The burden of gestational diabetes mellitus in Jamaican women with a family history of autosomol dominant type 2 diabetes - Irving, Rachael R....[et al.] (2008)
Seeks to determine whether Jamaican women of African descent with a family history of early onset autosomal dominant type 2 diabetes have greater odds of developing gestational diabetes mellitus (GDM) than those without a family history of the disease.